Tourism's income distribution in West Papua Province - Oscar Tiku; Tetsuo Shimizu; Djoni Hartono (Annals of Tourism Research Empirical Insights, 2022)
Pioneering the construction and application of social accounting matrix (SAM) framework in West Papua Province, Indonesia in 2018, this research aims to examine tourism-induced distribution effects on various socioeconomic groups by estimating SAM multiplier and its decomposition as well elaborating tourism influences through structural path analysis. Tourism brought significant impact on the economy with utmost overall contribution on capital factor and within decomposed cross multiplier effect. Nevertheless, impact on households decreases following a decrease in the level of household income. Accommodation and food services contributed on agricultural workers' income and employment. The latter has exceptional influence on the lowest-income rural household segment transmitted through fisheries, agricultural worker, and capital factor, that is strategic to improve livelihood and reducing regional poverty.
Keywords: 330; Income distribution; Multiplier decomposition; Social accounting matrix; Structural path analysis; Tourism; West Papua